Paracostal versus ventral midline approach for caudate liver lobectomy in the rabbit. Issue 6 (13th June 2022) - Leonard, Katherine C.; Zhao, Qianqian; Taber, Rachel H.; Colopy, Sara A.
Abstract: Objective: To describe the paracostal approach to caudate liver lobectomy in rabbits and compare the outcome of paracostal versus ventral midline approach for caudate liver lobectomy in rabbits with caudate liver lobe torsion (LLT). Study design: Cadaveric and retrospective study. Animals: Normal rabbit cadavers (n = 5) and rabbits with caudate LLT (n = 22). Methods: Cadavers – a right paracostal or ventral midline approach was made. Accessibility of the caudate liver lobe and relationship to the gastrointestinal (GI) tract were assessed. Clinical LLT cases – 9 cases were treated via the paracostal approach and 13 were treated via the ventral midline approach. Medical records (January, 2018 to October, 2021) were reviewed. Anesthesia and surgical times, mortality rate, and relevant clinical data were compared between groups. Results: In cadavers, caudate liver lobectomy was feasible through a paracostal approach without retraction of the GI tract. In clinical cases, there was no difference in anesthesia time ( P = 0.1397) or surgical time ( P = 0.9462) between groups. All rabbits that underwent paracostal approach survived to discharge. Mortality was lower ( P = .053) and postoperative time until eating was shorter ( P = .0238) for patients undergoing paracostal approach. Conclusion: Rabbits experienced lower mortality and shorter time until eating when treated through a right paracostal approach compared to the ventral midline approach. The paracostal approach resulted in minimal to no manipulation of the GI tract. Clinical significance: A right paracostal approach for caudate liver lobectomy in rabbits provides good exposure while avoiding GI tract manipulation. This approach may result in improved survival and earlier eating in rabbits with caudate LLT.